The effect of innovation on MSMEs in Cuenca, Ecuador. A transversal descriptive observational study - Astudillo, Silvana; Carpio, Ximena; Cordero, Fabián; Pozo, Santiago (Maskana, 2013)
This paper reports the results of an observational study assessing the effect of the introduction of innovation activities on business competitiveness and profitability in micro, small and medium enterprises, with application to the city of Cuenca. Distinction thereby was made between the effect of product innovation, process innovation, organizational, and marketing innovation. A descriptive transversal survey was performed in 156 companies during a 2-year period (2011-2012), using a predesigned questionnaire. Analysis revealed that innovations are more incremental than radical; basically related with product improvements and the introduction of new processes, incorporating mechanisms to promote improvements in marketing and business practices. Relations were not significant and the introduction of innovations did not yield in an increase in profitability during the survey period.